Quick-Wee method Versus Standard method for urine collection in infants 1-12 month old - Malla, Kalpana Karmacharya; Singh, Sandip Kumar; Chaudhary, Brajesh Raj; Ray, Nabal Kishore; Singh, Shivani (Nepal Mediciti Medical Journal, 2021)
BACKGROUND: Urinary Tract infections [UTI] often presents with fever and nonspecific findings in infants less than one year. So urine sample collection is mandatory for diagnosis or exclusion. Collecting Urine sample is very challenging in infants and choosing the method of collection must balance the reliability, speed and contamination. Clinical guidelines have different recommendations so there is a need for reliable collection method. Therefore this study was conducted to determine if a simple stimulation method (Quick–wee Method) increases the rate of clean catch voiding of urine within five minutes.METHODS: A prospective age and sex matched case control study in 1-12 months children conducted from June 2017 – June 2018 in Pediatric ward of Manipal college of medical sciences, Pokhara, after Ethical clearance from Institutional review Board [IRB]. The study population was randomized to either clean catch midstream urine with stimulation [Quick–Wee method] or without stimulation [Standard method]. The primary outcome was voiding of urine within 5 minute. Secondary outcome were waiting time for voiding, successful collection, parental satisfaction, and contamination. The analysis was done using SPSS version 20 and a ‘p’value